Data for "1,1,2-Ethenetriol: The Enol of Glycolic Acid, a High-Energy Prebiotic Molecule" - Schreiner, Peter; Justus Liebig University Giessen (My University, 2021)
Raw IR , UV/is and NMR spectra for the publication A. Mardyukov, F. Keul, and P. R. Schreiner "1,1,2-Ethenetriol: The Enol of Glycolic Acid, a High-Energy Prebiotic Molecule" . File format is the Bruker vibrational spectroscopy software OPUS for visualization, processing, analysis IR and UV/Vis data. File format is MestReNova NMR software for visualization, processing, analysis NMR data.
Keywords: enol; glycolic acid; prebiotic chemistry; ddc:540